(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article highlights the clinical significance of modern non-invasive diagnostic methods in the diagnosis and monitoring of Drug-Induced Liver Injury (DILI). It analyzes the role of transient elastography and serum biomarkers (specifically, humoral factors) in the early detection of hepatotoxicity developing against the background of polypharmacy, and in the assessment of necroinflammatory and fibrotic processes. The main focus is on diagnostic algorithms that provide a s1.afe and dynamic monitoring alternative to liver biopsy.